Neutron Imaging: A New Possibility for Laboratory Observation of Hydraulic Fractures in Shale?. Issue 4 (10th November 2018) - Roshankhah, S.; Marshall, J. P.; Tengattini, A.; Ando, E.; Rubino, V.; Rosakis, A. J.; Viggiani, G.; Andrade, J. E.
Abstract : Hydraulic fracturing (HF), the creation of fractures by high pressure fluid injection into a solid medium, is of interest to enhance the permeability of rocks. This complex 3D hydro-mechanical process, however, has only been studied in the lab by boundary measurements or acoustic techniques with low spatio-temporal resolutions until now. In this paper, direct, high spatial resolution, and near real-time visualization results of HF generation and propagation in prismatic specimens of Marcellus shale rock under in-situ conditions (3 km depth, plane strain) are presented. PMMA (Poly-Methyl Methacrylate) specimens are also tested under the same conditions to highlight the importance of internal structure on the response of the tested rock. The results reveal a complex interaction between the injected fluid, the pre-existing natural fractures in shales structure, and the hydraulically-induced fracture highlighting the governing role of rock fabric even under high stresses. These measurements are possible due to the unique sensitivity of neutrons to water. Besides the intrinsic interest of the results presented, this exploratory investigation highlights the potential of neutron imaging in elucidating the evolution of fluid flow and fluid-driven fractures, as X-rays have done for the evolution of solid structure only. Further, understanding of the mechanics of fracking will lead to development of more accurate hydro-mechanical constitutive models thus enabling the design of field operations with higher efficiencies.